A new species of Ctenobrycon Eigenmann, 1908 (Characiformes: Characidae) from the río Orinoco basin, Venezuela - Benine, Ricardo C. [UNESP]; Lopes, Guilherme A. M. [UNESP]; Ron, Ernesto (Magnolia Press, 2010)
Ctenobrycon oliverai, new species, is described from the río Orinoco drainage and its main tributary, río Apure, Venezuela. This species is readily distinguished from its congeners by the high number of series of scales above lateral line and by morphometric differences in body depth, head length, and interorbital distance. Statistical multivariate analysis was also conducted in order to test hypothesized differences among species of Ctenobrycon. A brief discussion on the taxonomy of this genus is provided. Copyright © 2010 · Magnolia Press.
Keywords: Ctenobrycon spilurus; Freshwater; Neotropical; Taxonomy